Exploring Indonesian Gen Z Digital Reading Issues - Dinda Ismu Asyifa (UICELL, 2020)
Generation Z is the youngest generation in this era. They have strong ability in technology. They can use technology for every activity they want, for the example in reading. They can read digitally through their screen by using their mobile phone, laptop, or computer. However, they prefer to read texts in digital form than printed texts, even though they're still facing some problems on it. This research explores Indonesian Gen Z digital reading issues. There are 235 youths’ participants of this research. The quantitative survey method was used in this research. The finding of this research showed that Indonesian Gen Z prefer to read in digital text through their mobile phone than printed text. Nonetheless, Indonesian Gen Z is still having some issues in digital reading.